Water electrolysis oxygen evolution catalyst with NiFe2O4-coated CoCr-LDH heterostructure and preparation method
Through the heterostructure recombination of NiFe2O4 and CoCr-LDH, the problem of low OER rate in electrocatalytic water decomposition is solved, the stability and activity of the catalyst are improved, and efficient electrolytic aquatic hydrogen is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411413945.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
In the existing electrocatalytic water decomposition technology, the rate of oxygen evolution reaction (OER) is limited by the kinetics of the multi-step proton coupled electron transfer process, resulting in the need of high overpotentials, the cost of precious metal catalysts is high and scarce, and non-precious metal catalysts are in the OER process. The stability and activity of the company limit its feasibility of industrial-scale applications.
By combining NiFe2O4 with excellent stability but poor activity with CoCr-LDH with excellent activity but insufficient stability, the heterostructure of NiFe2O4@CoCr-LDH was prepared by combining hydrothermal complexing and electrodeposition method. The electrolytic oxygen-induced catalyst improves the activity and stability of the catalyst.
A catalyst with high electrocatalytic activity and stability in alkaline electrolyte is realized, which reduces the energy consumption of electrolytic hydrogen, provides a larger catalytic surface area and optimized electron conduction path, and enhances the electrochemical activity of the electrode. Suitable for industrial applications.
Smart Images

Figure CN119287430A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a water electrolysis oxygen evolution catalyst with a NiFe2O4@CoCr-LDH heterostructure and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasingly serious environmental pollution problem, the development of new and efficient energy conversion technologies has become a top priority for development in the 21st century. In the pursuit of sustainable energy solutions, green hydrogen energy is regarded as an environmentally friendly alternative to traditional energy due to its clean and efficient characteristics, and its importance is gradually increasing. At present, green hydrogen energy has been widely researched and developed to address environmental pollution and energy consumption issues.
[0003] From the perspective of sustainable development of energy, electrocatalytic water splitting technology has significant strategic significance and practical value in achieving large-scale production and application of green hydrogen energy. Electrocatalytic water splitting technology has a history of nearly two centuries since its birth. Despite this, the proportion of hydrogen produced by this technology in the total output is only about 4%. Because in the entire electrocatalytic water splitting process, it is divided into two half reactions: hydrogen evolution reaction (HER) occurring at the cathode and oxygen evolution reaction (OER) occurring at the anode. In the two half reactions, OER is much slower than HER, and the rate of OER is greatly limited by the slow kinetics of the multi-step proton-coupled electron transfer process. A certain additional overpotential is required to overcome the activation energy barrier of the four-electron transfer reaction to promote this slow electrochemical reaction process. As one of the key half reactions in the water splitting process, the efficiency and stability of OER directly affect the performance of the entire water splitting system. However, at present, even the most advanced precious metal catalysts (RuO2, IrO2, etc.) still require a very high overpotential to overcome the energy barrier in the OER process. In addition, their scarcity and production cost also limit their feasibility in industrial-scale applications. Therefore, the development of non-precious metal electrocatalysts with excellent performance and low cost is of great significance for promoting the commercialization of electrocatalytic water splitting technology.
[0004] In recent years, transition metal materials have become a research hotspot in the field of electrocatalytic water splitting due to their cost-effectiveness. Among them, NiFe2O4, as a transition metal oxide, has received extensive attention in the field of OER due to its flexible sustainability, low cost, easy synthesis, structural / compositional diversity, high adsorption capacity, stability in alkaline solutions, earth abundance and environmental friendliness. Although the excellent catalytic stability of NiFe2O4 spinel materials has been revealed by relevant studies, its inherent fewer active sites and poor electrical conductivity restrict its large-scale application in the OER process. Based on NiFe2O4 spinel materials with excellent stability but poor activity, it is effectively compounded with OER catalytic materials with excellent activity but poor stability to construct a new highly active heterostructure, which is expected to further improve the OER catalytic performance of the material.
[0005] Layered double hydroxide (LDH) has excellent intrinsic electrocatalytic activity and unique microscopic lamellar structure, and is regarded as a promising candidate material for OER catalysts. The unique layered structure of LDH gives it a wider active interface, so it often exhibits excellent catalytic activity, but it is precisely because of the insufficient mechanical properties of the microscopic lamellar structure that its stability is relatively poor. Currently, the NiFe-LDH and NiCo-LDH systems are more studied, because the presence of nickel components can make the catalyst have acceptable stability while maintaining high activity. Although CoCr-LDH has excellent catalytic activity, its stability is not ideal and it cannot be used in conventional water electrolysis OER reactions. By compounding it with materials with better stability and constructing a heterogeneous structure, it is expected that these highly active LDH materials will break through the barrier of insufficient stability, thereby realizing their application in the field of water electrolysis and reducing the energy consumption of hydrogen production from water electrolysis.
[0006] In view of this, the present invention proposes a new alkaline water electrolysis oxygen evolution catalytic material, through reasonable process control, NiFe2O4 with good stability but poor activity is effectively compounded with CoCr-LDH with excellent activity but insufficient stability, to obtain a water electrolysis oxygen evolution catalyst with a NiFe2O4@CoCr-LDH heterostructure, which comprehensively improves the activity and stability of the catalyst and can effectively reduce the energy consumption of the water electrolysis hydrogen production process route. Summary of the invention
[0007] The object of the present invention is to provide a method for preparing a water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure. First, a metal current collector is combined with a NiFe2O4 spinel by a chemical method, and then CoCr-LDH nanosheets are in situ grown on the obtained NiFe2O4 spinel by an electrodeposition method, so as to finally obtain a high-performance alkaline water electrolysis oxygen evolution catalyst containing a NiFe2O4@CoCr-LDH heterostructure.
[0008] In order to achieve the above purpose, the technical solution adopted is:
[0009] A high-efficiency electrolytic oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure is prepared in two steps by combining a hydrothermal composite method with an accompanying heat treatment and an electrodeposition method. The specific preparation method comprises the following steps: (1) nickel salt, iron salt, ammonium fluoride and urea are added to water in a certain proportion and stirred evenly to obtain a mixed solution. (2) a clean foam substrate is immersed in the mixed solution, placed in a reactor at a certain hydrothermal temperature and hydrothermal time for hydrothermal composite, and a NiFe-LDH precursor is grown on the surface of the foam nickel. (3) the obtained sample is washed and dried, and then subjected to a heat treatment at an appropriate temperature to obtain a supported NiFe2O4 material. (4) the NiFe2O4 material is used as a working electrode, immersed in a reaction solution containing cobalt salt and chromium salt, and an electrodeposition reaction is performed to deposit a thin layer of CoCr-LDH nanosheets on the surface of the material. (5) the obtained working electrode is rinsed and dried to obtain the electrolytic oxygen evolution catalyst having the NiFe2O4@CoCr-LDH heterostructure.
[0010] Furthermore, the foam substrate is a foam substrate that has been cleaned in advance.
[0011] The foam substrate may be foam iron, foam copper, foam cobalt, foam nickel-iron alloy, etc., preferably foam nickel.
[0012] Furthermore, the molar ratio of the nickel salt to the iron salt is 1:0.5-3, preferably 1:2.
[0013] The nickel salt is one of nickel nitrate or its hydrate, nickel chloride or its hydrate.
[0014] The iron salt is one of ferric nitrate or its hydrate, ferric chloride or its hydrate.
[0015] Furthermore, the temperature of the re-high temperature heat treatment is 200-600°C, preferably 400°C.
[0016] Furthermore, the time of the high temperature heat treatment is 1 to 2 hours.
[0017] Furthermore, the molar ratio of the cobalt salt to the chromium salt is 1:0.5-3, preferably 1:2.
[0018] The cobalt salt is one of cobalt nitrate or its hydrate, cobalt chloride or its hydrate.
[0019] The chromium salt is one of chromium nitrate or its hydrate, chromium chloride or its hydrate.
[0020] Furthermore, the conditions of the electrodeposition reaction are: electrodeposition is carried out under the chronoamperometry at a voltage of -(1-1.2)V vs.Ag / AgCl and a time of 600-1600s, and the preferred electrodeposition voltage is -1.1V.
[0021] Furthermore, after the reaction is completed, the working electrode is rinsed with water and anhydrous ethanol, and then dried at 75 to 85° C. for 10 to 14 hours.
[0022] As described in the present invention, the catalyst for oxygen evolution by electrolysis of water obtained by the above preparation method has a spinel substrate obtained by high-temperature heat treatment of a NiFe-LDH composite precursor, which retains the electrochemical stability of the material to the greatest extent and enables it to have a certain catalytic reaction activity.
[0023] The NiFe2O4@CoCr-LDH heterostructure constructed by the method described in the present invention fully utilizes the chemical bond adsorption effect of NiFe2O4 and CoCr-LDH during the electrodeposition process, so that the active metal sites in the obtained catalyst are uniformly dispersed and firmly bonded, thereby maintaining high activity while ensuring stability, thereby improving the catalytic efficiency in the water electrolysis process.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The technical solution of the present invention adopts hydrothermal and electrodeposition steps to self-support the growth of NiFe2O4@CoCr-LDH on a foam substrate. The composite catalyst has the characteristics of high surface roughness and porosity, and can provide a larger catalytic surface area.
[0026] 2. The electrocatalyst described in the present invention has a CoCr-LDH flake thickness of less than 20 nanometers, which can be evenly spread on the surface of NiFe2O4 and form fin-like wrinkles. This unique micro-nano surface structure optimizes the conduction path of electrons on the electrode surface, while enhancing the interaction between the electrode and the electrolyte, expanding the electrochemically active surface area of the electrode, and thus providing stronger catalytic efficiency.
[0027] 3. According to the technical solution of the present invention, there is a strong interaction at the heterogeneous interface between NiFe2O4 and CoCr-LDH, which helps to optimize and adjust the electronic properties and catalytic performance of the composite material. This not only improves the electron transmission capacity of the electrode, but also reduces the impedance of interfacial charge transfer, facilitates the rapid transfer of electrons in the electrocatalytic process, and enables the originally unstable CoCr-LDH to work stably for a long time in the OER electrocatalytic environment.
[0028] 4. The technical solution of the present invention provides an electrocatalyst with good electrocatalytic activity and stability in alkaline electrolyte at high current density, which provides new possibilities for industrialization and also provides valuable guidance for the design and optimization of efficient energy conversion electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 X-ray diffraction patterns of NiFe2O4@CoCr-LDH / NF with different electrodeposition times;
[0030] Figure 2 The scanning electron microscope image of NiFe2O4@CoCr-LDH / NF with electrodeposition time of 1000s;
[0031] Figure 3 The full XPS spectra of NiFe2O4, CoCr-LDH and NiFe2O4@CoCr-LDH / NF-1000;
[0032] Figure 4 are the oxygen evolution overpotentials and Tafel slopes of the five catalysts under alkaline conditions;
[0033] Figure 5 The OER stability of the optimal catalyst under alkaline conditions. DETAILED DESCRIPTION
[0034] The present invention provides a water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure and a preparation method. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0035] The following will further introduce in detail the water electrolysis oxygen evolution catalyst and preparation method with NiFe2O4@CoCr-LDH heterostructure provided by the present invention in combination with specific embodiments:
[0036] A method for preparing a water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure, characterized in that it comprises the following steps: (1) adding nickel salt, iron salt, ammonium fluoride and urea to water in a certain proportion and stirring evenly to obtain a mixed solution. (2) immersing a clean foam substrate in the mixed solution, placing it in a reactor for hydrothermal compounding at a certain hydrothermal temperature and hydrothermal time, and growing a NiFe-LDH precursor on the surface of the foam nickel. (3) washing and drying the obtained sample, and then performing a heat treatment at an appropriate temperature to obtain a supported NiFe2O4 material. (4) using the NiFe2O4 material as a working electrode, immersing it in a reaction solution containing cobalt salt and chromium salt, performing an electrodeposition reaction, and depositing a thin layer of CoCr-LDH nanosheets on the surface of the material. The obtained working electrode is rinsed and dried to obtain the water electrolysis oxygen evolution catalyst having the NiFe2O4@CoCr-LDH heterostructure.
[0037] The foam base is a clean foam base;
[0038] The foam substrate may be foam iron, foam copper, foam cobalt, foam nickel-iron alloy, etc., preferably foam nickel;
[0039] Furthermore, the molar ratio of the nickel salt to the iron salt is 1:0.5-3, preferably 1:2.
[0040] The nickel salt is one of nickel nitrate or its hydrate, nickel chloride or its hydrate;
[0041] The iron salt is one of ferric nitrate or its hydrate, ferric chloride or its hydrate.
[0042] Furthermore, the temperature of the high temperature oven heat treatment is 200-600°C, preferably 400°C;
[0043] Furthermore, the time of the high-temperature oven heat treatment is 1 to 2 hours.
[0044] Furthermore, the molar ratio of the cobalt salt to the chromium salt is 1:0.5 to 3, preferably 1:2.
[0045] The cobalt salt is one of cobalt nitrate or its hydrate, cobalt chloride or its hydrate;
[0046] The chromium salt is one of chromium nitrate or its hydrate, chromium chloride or its hydrate.
[0047] In a further aspect, the conditions of the electrodeposition reaction are: electrodeposition is carried out under the chronoamperometry method at a voltage of -(1-1.2)V vs.Ag / AgCl and a time of 600-1600s. The preferred voltage is -1.1V.
[0048] Furthermore, after the reaction is completed, the working electrode is rinsed with water and anhydrous ethanol, and then dried at 75 to 85° C. for 10 to 14 hours.
[0049] The electrocatalyst prepared above adopts simple hydrothermal and electrodeposition steps to prepare 2D-core-shell NiFe2O4@CoCr-LDH. The construction of heterogeneous structure makes full use of the characteristics of the two materials and produces a certain synergistic effect, which significantly improves the electrocatalytic performance. Therefore, in alkaline electrolyte, at 10mA cm -2 The overpotential is 239mV.
[0050] The specific embodiments are as follows:
[0051] Example 1
[0052] The water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure and the preparation method thereof described in the present invention specifically include the following steps:
[0053] (1) Clean pretreatment of nickel foam: Cut 1×2 cm nickel foam into 1M NaOH solution, hydrothermally treat at 100°C for 2 h, then remove and ultrasonically clean with anhydrous ethanol and deionized water for 10 min respectively, and then dry in an oven at 80°C.
[0054] (2) Synthesis of NiF-LDH@NF: 3.6mmolNi(NO3)2·6H2O, 7.2mmolFe(NO3)3·9H2O, 2mmolNH4F and 12.6mmolCH4N2O were dissolved in 100ml ultrapure water for 30min to obtain a transparent solution. The solution and the clean nickel foam were transferred to a polytetrafluoroethylene-lined stainless steel reactor. The reactor was sealed and heated in an oven at 100℃ for 12h and naturally cooled to room temperature in the oven. Finally, NiFe-LDH-loaded NF was obtained, and the NiFe-LDH-loaded NF material was vacuum dried at a constant temperature of 80℃ for 12h to prepare the NiFe-LDH@NF composite material.
[0055] (3) Preparation of NiFe2O4@NF: The prepared NiFe-LDH@NF composite material was calcined in a muffle furnace at 400°C for 1 to 2 h to obtain a NiFe2O4@NF composite material.
[0056] (4) Preparation of NiFe2O4@CoCr-LDH / NF: The above NiFe2O4@NF was used as the working electrode, the platinum mesh was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrodeposition was carried out in a mixed solution of 1.8mmolCo(NO3)2·6H2O and 3.6mmolCrCl3·6H2O at a voltage of -1.1V for 1000s. The electrodeposited material was taken out from the solution, rinsed with deionized water, and vacuum dried at a constant temperature of 80°C for 12 hours to prepare the NiFe2O4@CoCr-LDH / NF-1000 composite material.
[0057] The alkaline water electrolysis catalyst obtained in Example 1 was scanned and analyzed. Figure 2 It can be seen that NiFe2O4@CoCr-LDH / NF maintains a nanoflower-like morphology similar to that of NiFe2O4 / NF, and a layer of CoCr-LDH network structure is formed on its surface.
[0058] Example 1: The X-ray photoelectron spectrometer image of the alkaline water electrolysis catalyst is obtained, as shown in FIG. Figure 3 It can be seen that the corresponding elements can be found in the XPS graph, which can also prove that each level of products are successfully prepared and finally successfully compounded.
[0059] The alkaline water electrolysis catalyst obtained in Example 1 was subjected to OER test in 1M KOH, with the prepared catalyst as the working electrode, Hg / HgO as the reference electrode, and Pt mesh as the counter electrode. Figure 4 As shown, at 10 mA cm -2 , 50mA cm -2 , 100mA cm -2 The overpotentials at current densities are 239 mV, 280 mV, and 321 mV, respectively. NiFe2O4@CoCr-LDH / NF-1000 has the lowest overpotential and the smallest Tafel slope, which corresponds to the OER reaction kinetics.
[0060] The alkaline water electrolysis catalyst obtained in Example 1 was tested for stability by chronoamperometry in 1M KOH. The results are as follows: Figure 5 As shown, the alkaline water electrolysis catalyst NiFe2O4@CoCr-LDH / NF-1000 prepared in Example 1 was used as the working electrode, Hg / HgO was used as the reference electrode, and Pt mesh was used as the counter electrode. -2 In the IT test under current density of 48h, the overpotential did not change significantly, indicating that the invented catalysts have good stability under alkaline conditions.
[0061] Example 2
[0062] The water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure and the preparation method thereof described in the present invention specifically include the following steps:
[0063] (1) Clean pretreatment of nickel foam: Cut 1×2 cm nickel foam into 1M NaOH solution, hydrothermally treat at 100°C for 2 h, then remove and ultrasonically clean with anhydrous ethanol and deionized water for 10 min respectively, and then dry in an oven at 80°C.
[0064] (2) Synthesis of NiF-LDH@NF: 3.6mmolNi(NO3)2·6H2O, 7.2mmolFe(NO3)3·9H2O, 2mmolNH4F and 12.6mmolCH4N2O were dissolved in 100ml ultrapure water for 30min to obtain a transparent solution. The solution and the clean nickel foam were transferred to a polytetrafluoroethylene-lined stainless steel reactor. The reactor was sealed and heated in an oven at 100℃ for 12h and naturally cooled to room temperature in the oven. Finally, NiFe-LDH-loaded NF was obtained, and the NiFe-LDH-loaded NF material was vacuum dried at a constant temperature of 80℃ for 12h to prepare the NiFe-LDH@NF composite material.
[0065] (3) Preparation of NiFe2O4@NF: The prepared NiFe-LDH@NF composite material was calcined in a muffle furnace at 400°C for 1 to 2 h to obtain a NiFe2O4@NF composite material.
[0066] (4) Preparation of NiFe2O4@CoCr-LDH / NF: The above NiFe2O4@NF was used as the working electrode, the platinum mesh was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrodeposition was carried out in a mixed solution of 1.8mmolCo(NO3)2·6H2O and 3.6mmolCrCl3·6H2O at a voltage of -1.1V for 600s. The electrodeposited material was taken out from the solution, rinsed with deionized water, and vacuum dried at a constant temperature of 80°C for 12 hours to prepare the NiFe2O4@CoCr-LDH / NF-600 composite material.
[0067] The alkaline water electrolysis catalyst obtained in Example 2 was subjected to OER test in 1M KOH, with the prepared catalyst as the working electrode, Hg / HgO as the reference electrode, and Pt mesh as the counter electrode. Figure 4 As shown, at 10 mA cm -2 , 50mA cm -2 , 100mA cm -2 The overpotentials at current densities are 244mV, 293mV, and 344mV respectively.
[0068] Example 3
[0069] The water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure and the preparation method thereof described in the present invention specifically include the following steps:
[0070] (1) Clean pretreatment of nickel foam: Cut 1×2 cm nickel foam into 1M NaOH solution, hydrothermally treat at 100°C for 2 h, then remove and ultrasonically clean with anhydrous ethanol and deionized water for 10 min respectively, and then dry in an oven at 80°C.
[0071] (2) Synthesis of NiF-LDH@NF: 3.6mmolNi(NO3)2·6H2O, 7.2mmolFe(NO3)3·9H2O, 2mmolNH4F and 12.6mmolCH4N2O were dissolved in 100ml ultrapure water for 30min to obtain a transparent solution. The solution and the clean nickel foam were transferred to a polytetrafluoroethylene-lined stainless steel reactor. The reactor was sealed and heated in an oven at 100℃ for 12h and naturally cooled to room temperature in the oven. Finally, NiFe-LDH-loaded NF was obtained, and the NiFe-LDH-loaded NF material was vacuum dried at a constant temperature of 80℃ for 12h to prepare the NiFe-LDH@NF composite material.
[0072] (3) Preparation of NiFe2O4@NF: The prepared NiFe-LDH@NF composite material was calcined in a muffle furnace at 400°C for 1 to 2 h to obtain a NiFe2O4@NF composite material.
[0073] (4) Preparation of NiFe2O4@CoCr-LDH / NF: The above NiFe2O4@NF was used as the working electrode, the platinum mesh was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrodeposition was carried out in a mixed solution of 1.8mmolCo(NO3)2·6H2O and 3.6mmolCrCl3·6H2O at a voltage of -1.1V for 800s. The electrodeposited material was taken out from the solution, rinsed with deionized water, and vacuum dried at a constant temperature of 80°C for 12 hours to prepare the NiFe2O4@CoCr-LDH / NF-800 composite material.
[0074] The alkaline water electrolysis catalyst obtained in Example 3 was subjected to OER test in 1M KOH, with the prepared catalyst as the working electrode, Hg / HgO as the reference electrode, and Pt mesh as the counter electrode. Figure 4 As shown, at 10 mA cm -2 , 50mA cm -2 , 100mA cm -2 The overpotentials at current densities are 237mV, 281mV, and 326mV respectively.
[0075] Example 4
[0076] The water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure and the preparation method thereof described in the present invention specifically include the following steps:
[0077] (1) Clean pretreatment of nickel foam: Cut 1×2 cm nickel foam into 1M NaOH solution, hydrothermally treat at 100°C for 2 h, then remove and ultrasonically clean with anhydrous ethanol and deionized water for 10 min respectively, and then dry in an oven at 80°C.
[0078] (2) Synthesis of NiF-LDH@NF: 3.6mmolNi(NO3)2·6H2O, 7.2mmolFe(NO3)3·9H2O, 2mmolNH4F and 12.6mmolCH4N2O were dissolved in 100ml ultrapure water for 30min to obtain a transparent solution. The solution and the clean nickel foam were transferred to a polytetrafluoroethylene-lined stainless steel reactor. The reactor was sealed and heated in an oven at 100℃ for 12h and naturally cooled to room temperature in the oven. Finally, NiFe-LDH-loaded NF was obtained, and the NiFe-LDH-loaded NF material was vacuum dried at a constant temperature of 80℃ for 12h to prepare the NiFe-LDH@NF composite material.
[0079] (3) Preparation of NiFe2O4@NF: The prepared NiFe-LDH@NF composite material was calcined in a muffle furnace at 400°C for 1 to 2 h to obtain a NiFe2O4@NF composite material.
[0080] (4) Preparation of NiFe2O4@CoCr-LDH / NF: The above NiFe2O4@NF was used as the working electrode, the platinum mesh was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrodeposition was carried out in a mixed solution of 1.8mmolCo(NO3)2·6H2O and 3.6mmolCrCl3·6H2O at a voltage of -1.1V for 1200s. The electrodeposited material was taken out from the solution, rinsed with deionized water, and vacuum dried at a constant temperature of 80°C for 12 hours to prepare the NiFe2O4@CoCr-LDH / NF-1200 composite material.
[0081] The alkaline water electrolysis catalyst obtained in Example 4 was subjected to OER test in 1M KOH, with the prepared catalyst as the working electrode, Hg / HgO as the reference electrode, and Pt mesh as the counter electrode. Figure 4 As shown, at 10 mA cm -2 , 50mA cm -2 , 100mA cm -2 The overpotentials at current densities are 241mV, 287mV, and 335mV respectively.
[0082] Example 5
[0083] The water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure and the preparation method thereof described in the present invention specifically include the following steps:
[0084] (1) Clean pretreatment of nickel foam: Cut 1×2 cm nickel foam into 1M NaOH solution, hydrothermally treat at 100°C for 2 h, then remove and ultrasonically clean with anhydrous ethanol and deionized water for 10 min respectively, and then dry in an oven at 80°C.
[0085] (2) Synthesis of NiF-LDH@NF: 3.6mmolNi(NO3)2·6H2O, 7.2mmolFe(NO3)3·9H2O, 2mmolNH4F and 12.6mmolCH4N2O were dissolved in 100ml ultrapure water for 30min to obtain a transparent solution. The solution and the clean nickel foam were transferred to a polytetrafluoroethylene-lined stainless steel reactor. The reactor was sealed and heated in an oven at 100℃ for 12h and naturally cooled to room temperature in the oven. Finally, NiFe-LDH-loaded NF was obtained, and the NiFe-LDH-loaded NF material was vacuum dried at a constant temperature of 80℃ for 12h to prepare the NiFe-LDH@NF composite material.
[0086] (3) Preparation of NiFe2O4@NF: The prepared NiFe-LDH@NF composite material was calcined in a muffle furnace at 400°C for 1 to 2 h to obtain a NiFe2O4@NF composite material.
[0087] (4) Preparation of NiFe2O4@CoCr-LDH / NF: The above NiFe2O4@NF was used as the working electrode, the platinum mesh was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrodeposition was carried out in a mixed solution of 1.8mmolCo(NO3)2·6H2O and 3.6mmolCrCl3·6H2O at a voltage of -1.1V for 1400s. The electrodeposited material was taken out from the solution, rinsed with deionized water, and vacuum dried at a constant temperature of 80°C for 12 hours to prepare the NiFe2O4@CoCr-LDH / NF-1400 composite material.
[0088] The alkaline water electrolysis catalyst obtained in Example 5 was subjected to OER test in 1M KOH, with the prepared catalyst as the working electrode, Hg / HgO as the reference electrode, and Pt mesh as the counter electrode. Figure 4 As shown, at 10 mA cm -2 , 50mA cm -2 , 100mA cm -2 The overpotentials at current densities are 249mV, 307mV, and 370mV respectively.
[0089] Example 6
[0090] The water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure and the preparation method thereof described in the present invention specifically include the following steps:
[0091] (1) Clean pretreatment of nickel foam: Cut 1×2 cm nickel foam into 1M NaOH solution, hydrothermally treat at 100°C for 2 h, then remove and ultrasonically clean with anhydrous ethanol and deionized water for 10 min respectively, and then dry in an oven at 80°C.
[0092] (2) Synthesis of NiF-LDH@NF: 3.6mmolNi(NO3)2·6H2O, 1.8mmolFe(NO3)3·9H2O, 2mmolNH4F and 12.6mmolCH4N2O were dissolved in 100ml ultrapure water for 30min to obtain a transparent solution. The solution and the clean nickel foam were transferred to a polytetrafluoroethylene-lined stainless steel reactor. The reactor was sealed and heated in an oven at 100℃ for 12h and naturally cooled to room temperature in the oven. Finally, NiFe-LDH-loaded NF was obtained, and the NiFe-LDH-loaded NF material was vacuum dried at a constant temperature of 80℃ for 12h to prepare the NiFe-LDH@NF composite material.
[0093] (3) Preparation of NiFe2O4@NF: The prepared NiFe-LDH@NF composite material was calcined in a muffle furnace at 400°C for 1 to 2 h to obtain a NiFe2O4@NF composite material.
[0094] (4) Preparation of NiFe2O4@CoCr-LDH / NF: The above NiFe2O4@NF was used as the working electrode, the platinum mesh was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrodeposition was carried out in a mixed solution of 1.8mmolCo(NO3)2·6H2O and 3.6mmolCrCl3·6H2O at a voltage of -1V for 1000s. The electrodeposited material was taken out from the solution, rinsed with deionized water, and vacuum dried at a constant temperature of 80°C for 12 hours to prepare the NiFe2O4@CoCr-LDH / NF composite material.
[0095] The alkaline water electrolysis catalyst obtained in Example 6 was subjected to OER test in 1M KOH, with the prepared catalyst as the working electrode, Hg / HgO as the reference electrode, and Pt mesh as the counter electrode. -2 , 50mA cm -2 , 100mA cm -2 The overpotentials at current densities are 255mV, 299mV, and 346mV respectively.
[0096] Example 7
[0097] The water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure and the preparation method thereof described in the present invention specifically include the following steps:
[0098] (1) Clean pretreatment of nickel foam: Cut 1×2 cm nickel foam into 1M NaOH solution, hydrothermally treat at 100°C for 2 h, then remove and ultrasonically clean with anhydrous ethanol and deionized water for 10 min respectively, and then dry in an oven at 80°C.
[0099] (2) Synthesis of NiF-LDH@NF: 3.6mmolNi(NO3)2·6H2O, 7.2mmolFe(NO3)3·9H2O, 2mmolNH4F and 12.6mmolCH4N2O were dissolved in 100ml ultrapure water for 30min to obtain a transparent solution. The solution and the clean nickel foam were transferred to a polytetrafluoroethylene-lined stainless steel reactor. The reactor was sealed and heated in an oven at 100℃ for 12h and naturally cooled to room temperature in the oven. Finally, NiFe-LDH-loaded NF was obtained, and the NiFe-LDH-loaded NF material was vacuum dried at a constant temperature of 80℃ for 12h to prepare the NiFe-LDH@NF composite material.
[0100] (3) Preparation of NiFe2O4@NF: The prepared NiFe-LDH@NF composite material was calcined in a muffle furnace at 400°C for 1 to 2 h to obtain a NiFe2O4@NF composite material.
[0101] (4) Preparation of NiFe2O4@CoCr-LDH / NF: The above NiFe2O4@NF was used as the working electrode, the platinum mesh was used as the counter electrode, and Ag / AgCl was used as the reference electrode. The electrodeposition was carried out in a mixed solution of 1.8mmolCo(NO3)2·6H2O and 1.8mmolCrCl3·6H2O at a voltage of -1V for 1000s. The electrodeposited material was taken out from the solution, rinsed with deionized water, and vacuum dried at a constant temperature of 80°C for 12 hours to prepare the NiFe2O4@CoCr-LDH / NF composite material.
[0102] The alkaline water electrolysis catalyst obtained in Example 7 was subjected to OER test in 1M KOH, with the prepared catalyst as the working electrode, Hg / HgO as the reference electrode, and Pt mesh as the counter electrode. -2 , 50mA cm -2 , 100mA cm -2 The overpotentials at current densities are 240mV, 295mV, and 333mV respectively.
[0103] Example 8
[0104] X-ray detection was performed on the alkaline water electrolysis catalysts obtained in Examples 1-5 with different electrodeposition times. The results are as follows: Figure 1 As shown, in addition to the characteristic peaks from (111), (200) and (220) crystal planes belonging to nickel foam, there are also characteristic peaks from (311), (400) and (440) crystal planes belonging to NiFe2O4. The reason why there is no obvious characteristic peak of CoCr-LDH is that the characteristic peak of NF is too strong, resulting in the characteristic peak of CoCr-LDH on electrodeposition being unclear. The results show that the products of various levels were successfully prepared and synthesized.
[0105] The above is only a preferred embodiment of the embodiment of the present invention, and does not impose any form of limitation on the embodiment of the present invention. Any simple modification, equivalent changes and modifications made to the above embodiment based on the technical essence of the embodiment of the present invention are still within the scope of the technical solution of the embodiment of the present invention.
Claims
1. A method for preparing a water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure, characterized in that: The following steps are involved: (a) adding nickel salt, iron salt, ammonium fluoride and urea into water and stirring to form a uniform solution, wherein the molar ratio of nickel salt to iron salt is controlled within the range of 1:0.5 to 3; (b) immersing the clean foam metal substrate in the mixed solution obtained in step (a), and then placing it in a reaction kettle for hydrothermal compounding at a certain temperature and time to grow NiFe-LDH precursor flakes on the surface of the foam nickel; (c) washing and drying the obtained sample, and then heat treating it at 200-600° C. for 1-2 h to obtain a NiFe2O4 material tightly bonded to the foam metal; (d) using NiFe2O4 material as a working electrode, immersing it in a mixed solution of cobalt salt and chromium salt prepared in the ratio according to claim 1, and performing an electrodeposition treatment at a voltage of -(1-1.2)V vs.Ag / AgCl for a deposition time of 600-1600 seconds to prepare and immobilize CoCr-LDH fin-shaped nanosheets on the surface of nickel-iron spinel; (e) The obtained working electrode is rinsed with water and anhydrous ethanol, and dried at a low temperature of 75 to 85° C. for a sufficiently long time to obtain the electrolytic water oxygen evolution catalyst having the NiFe2O4@CoCr-LDH heterostructure.
2. The method for preparing a water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure according to claim 1, characterized in that: The nickel salt is one of nickel nitrate or its hydrate, nickel chloride or its hydrate; the iron salt is one of iron nitrate or its hydrate, iron chloride or its hydrate.
3. The method for preparing the water electrolysis oxygen evolution catalyst having the NiFe2O4@CoCr-LDH heterostructure according to claim 1, characterized in that: The foam metal substrate can be foam iron, foam copper, foam cobalt, foam nickel-iron alloy, etc.
4. The method for preparing the water electrolysis oxygen evolution catalyst having the NiFe2O4@CoCr-LDH heterostructure according to claim 1, characterized in that: The cobalt salt is one of cobalt nitrate or its hydrate, cobalt chloride or its hydrate; the chromium salt is one of chromium nitrate or its hydrate, chromium chloride or its hydrate.
5. A water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure, characterized in that: The catalyst is prepared by the preparation method as described in any one of claims 1 to 4, wherein the NiFe2O4 spinel carrier is obtained by calcining a nickel-iron layered double hydroxide precursor at a moderately high temperature, the cobalt-chromium feed molar ratio of CoCr-LDH in the catalyst is 1:0.5-3, and is fixed on the surface of the NiFe2O4 spinel plate by electrodeposition and evenly spread in the form of nano-fins.
6. The water electrolysis oxygen evolution catalyst having a NiFe2O4@CoCr-LDH heterostructure according to claim 5, characterized in that: The catalyst can provide excellent electrocatalytic activity and stability for oxygen evolution reaction in water electrolysis under alkaline environment, and can be widely used as oxygen evolution electrode material in water electrolysis hydrogen production process.